Jahresbericht des Vereins Kunsthalle Bern 1987 / 88. - Loock, Ulrich; Kunsthalle Bern (Bern : Kunsthalle Bern, 1988)
Berger, Ueli ; Baumgarten, Lothar ; Daniëls, René ; Struth, Thomas ; West, Franz ; Pozarek, Vaclav ; Moser, Jürg ; Schnider, Albrecht ; Lindow, Christian ; etc.
Duits
boek